Implementasi Mesin Pengiris Keripik Tempe Untuk Meningkatkan Produktivitas UKM Tempe - Ibrohim, Ibrohim; Pramono, Made; Budijono, Agung Prijo; Kurniawan, Wahyu Dwi (Fakultas Teknik Universitas Negeri Surabaya, 2019)
Tempe chips is one snack that is popular with all groups. During this time the process of slicing tempe chips is still using the conventional method using a hand knife. This resulted in the ineffectiveness of the process of slicing the tempe stem which is the basic ingredient of tempe chips with a relatively long duration of Â± 30 slices/minute. Besides that, Â± 10% -15% slices have varied thicknesses and are relatively thick (3mm), which causes crispy tempe chips. Due to constraints in the process of cutting tempeh, SMEs can only produce 10kg / day and cannot meet market needs that reach twice the current SME production. In addition, because the cutting process is done manually, it requires a large amount of power, a long time, not hygienic and prone to work accidents. To overcome the problems of partners, the partner SMEs will be assisted through the design of tempe chip slicing machines. The method of carrying out this activity is designing, manufacturing, assembly, testing of machines, handover of machines, training in operation and maintenance of machines, and periodic monitoring. Based on the results of implementation in the SME tempe chips manufacturer, the tempe chip slicing machine really helped solve the problem of the tempe chips SME producer. This can be seen from the practicality of the slicing process which requires a relatively fast time of 60 slices / minute so that employees are not easily exhausted. It also improves the quality of tempe chips, where uniform thickness of tempe chips is 2mm and is more hygienic because the machine material is made of foodgrade stainless steel standards. Some of these advantages have an impact on production capacity that has doubled from 10kg / day to 20 kg / day.